Unnatural history: is a paradigm shift of natural history in 21st century ornithology needed?. (6th March 2018) - Callaghan, Corey T.; Martin, John M.; Kingsford, Richard T.; Brooks, Daniel M.
Abstract : Natural history, across disciplines, is essential for the continuation of science, especially as we attempt to identify the myriad of threats that biodiversity faces in this rapidly changing world. Recording the natural history of birds is perhaps the most prominent, widespread and long‐standing pursuit of this activity. Yet, there is a distinct decrease in publishing of natural history in the ornithological sciences. Concomitantly, the natural history information being published is often in small and regional journals, less accessible by the global ornithological community. We argue that historical natural history needs a modern reinvigoration, and should focus on placing natural history observations in the context of an anthropogenically altered world – 'unnatural history'. This includes, but is not limited to, behavioural adaptations, novel diet choices, hybridization and novel adaptations to urbanization. Here, we elaborate on natural history's place in modern ornithology, how this relates to citizen science and the potential cost of ignoring it. Ultimately, increased accessibility of natural history observations, encouragement of amateur ornithologists' participation in professional societies (and vice versa) and targeted citizen science projects are potential mechanisms by which to reinvigorate natural history in 21st century ornithology.